Discovering Family Lineage - Bakken, Patrick (My University, 2013)
Today, the 200-year-old Bakken Mill is still standing strong and operational. In the summer of 2011, I traveled to Norway to research my family’s lineage and attend an international family reunion. It was truly a spectacle. Being in the physical place where your family started was sensational. It is something that I wish everyone has a chance to do in his or her lifetime. I was fortunate and able to spend more than my originally planned time over there. In total, I spent a month living with and traveling in Norway with my long lost family; learning about Norwegians and the culture I came from, as well as the people in my ancestry.
Abstract Only